PENERAPAN MODEL PEMBELAJARAN SEARCH SOLVE CREATE SHARE (SSCS) MELALUI PENDEKATAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR IPA BIOLOGI KELAS VIII SMPN 007 BAMBANG MAMASA - Jiltasari Jiltasari; Husain As; Ninah Wahyuni Amaliah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
This classroom action research (CAR) includes planning, implementation, observation, and reflection activities carried out at SMPN 007 Bambang Mamasa. This study aims to improve Biology Science Learning Outcomes for Class VIII Students of SMPN 007 Bambang Mamasa, through the application of the SSCS Learning Model with a Problem Solving Approach. Data collection was carried out through student learning outcomes tests at the end of the cycle and student observation sheets at each meeting. The analysis used is qualitative and quantitative statistical analysis. The results of this study indicate that: the average score of the student learning outcomes test in the first cycle is 55.60 which is in the low category. The lowest score obtained by students is 35 and the highest score is 85 from the ideal score of 100. In the first cycle, 21 students did not complete and 4 students completed. Then in cycle II the average score of student learning outcomes test results has a very high increase, which is 78.60. Where the lowest score obtained by students is 60 and the highest score is 90 from the ideal score of 100. In the second cycle, 2 students did not complete and 23 students completed. This shows that using the SSCS learning model through a problem solving approach can improve student learning outcomes for class VIII SMPN 007 Bambang Mamasa Mamasa.